Targeting Emerging RNA Viruses by Engineered Human Superantibody to Hepatitis C Virus RNA-Dependent RNA Polymerase - Glab-ampai, Kittirat; Kaewchim, Kanasap; Thavorasak, Techit; Saenlom, Thanatsaran; Thepsawat, Watayagorn; Mahasongkram, Kodchakorn; Thueng-In, Kanyarat; Sookrung, Nitat; Chaicumpa, Wanpen; Chulanetra, Monrat (Frontiers in Microbiology, 2022)
RNA-dependent RNA polymerase (RdRp) is a unique and highly conserved enzyme across all members of the RNA virus superfamilies. Besides, humans do not have a homolog of this protein. Therefore, the RdRp is an attractive target for a broadly effective therapeutic agent against RNA viruses. In this study, a formerly generated cell-penetrating human single-chain antibody variable fragment (superantibody) to a conformational epitope of hepatitis C virus (HCV) RdRp, which inhibited the polymerase activity leading to the HCV replication inhibition and the host innate immunity restoration, was tested against emerging/reemerging RNA viruses. The superantibody could inhibit the replication of the other members of the Flaviviridae (DENV serotypes 1−4, ZIKV, and JEV), Picornaviridae (genus Enterovirus: EV71, CVA16), and Coronaviridae (genus Alphacoronavirus: PEDV, and genus Betacoronavirus: SARS-CoV-2 (Wuhan wild-type and the variants of concern), in a dose-dependent manner, as demonstrated by the reduction of intracellular viral RNAs and numbers of the released infectious particles. Computerized simulation indicated that the superantibody formed contact interfaces with many residues at the back of the thumb domain (thumb II site, T2) of DENV, ZIKV, JEV, EV71, and CVA16 and fingers and thumb domains of the HCV and coronaviruses (PEDV and SARS-CoV-2). The superantibody binding may cause allosteric change in the spatial conformation of the enzyme and disrupt the catalytic activity, leading to replication inhibition. Although the speculated molecular mechanism of the superantibody needs experimental support, existing data indicate that the superantibody has high potential as a non-chemical broadly effective anti-positive sense-RNA virus agent.